Population-genetic comparison of the Sorbian isolate population in Germany with the German KORA population using genome-wide SNP arrays - Gross, Arnd; Tönjes, Anke; Kovacs, Peter; Veeramah, Krishna R; Ahnert, Peter; Roshyara, Nab R; Gieger, Christian; Rueckert, Ina-Maria; Loeffler, Markus; Stoneking, Mark; Wichmann, Heinz-Erich; Novembre, John; et al. (BMC genetics, 2011)
BACKGROUND: The Sorbs are an ethnic minority in Germany with putative genetic isolation, making the population interesting for disease mapping. A sample of N = 977 Sorbs is currently analysed in several genome-wide meta-analyses. Since genetic differences between populations are a major confounding factor in genetic meta-analyses, we compare the Sorbs with the German outbred population of the KORA F3 study (N = 1644) and other publically available European HapMap populations by population genetic means. We also aim to separate effects of over-sampling of families in the Sorbs sample from effects of genetic isolation and compare the power of genetic association studies between the samples. RESULTS: The degree of relatedness was significantly higher in the Sorbs. Principal components analysis revealed a west to east clustering of KORA individuals born in Germany, KORA individuals born in Poland or Czech Republic, Half-Sorbs (less than four Sorbian grandparents) and Full-Sorbs. The Sorbs cluster is nearest to the cluster of KORA individuals born in Poland. The number of rare SNPs is significantly higher in the Sorbs sample. FST between KORA and Sorbs is an order of magnitude higher than between different regions in Germany. Compared to the other populations, Sorbs show a higher proportion of individuals with runs of homozygosity between 2.5 Mb and 5 Mb. Linkage disequilibrium (LD) at longer range is also slightly increased but this has no effect on the power of association studies. Oversampling of families in the Sorbs sample causes detectable bias regarding higher FST values and higher LD but the effect is an order of magnitude smaller than the observed differences between KORA and Sorbs. Relatedness in the Sorbs also influenced the power of uncorrected association analyses. CONCLUSIONS: Sorbs show signs of genetic isolation which cannot be explained by over-sampling of relatives, but the effects are moderate in size. The Slavonic origin of the Sorbs is still genetically detectable. Regarding LD structure, a clear advantage for genome-wide association studies cannot be deduced. The significant amount of cryptic relatedness in the Sorbs sample results in inflated variances of Beta-estimators which should be considered in genetic association analyses.
Keywords: dospělí; Germany; Phenotype; Population Groups; etnicita; Ethnicity; Adult; Polsko; jednonukleotidový polymorfismus; lidé; populační skupiny; Polymorphism, Single Nucleotide; Německo; Genetics, Population; Aged; Czech Republic; Principal Component Analysis; Česká republika; lidé středního věku; analýza hlavních komponent; senioři; fenotyp; Poland; Middle Aged; populační genetika; Humans